Kinetics of phase transformations in lead scandium tantalate thin films - Battat, J.; Huang, Zhaorong; Donohue, P. P.; Todd, M. A.; Whatmore, Roger W. (Taylor and Francis, 2004)
The phase transformations from amorphous to pyrochlore to perovskite in lead scandium tantalate (PST) thin films during rapid thermal annealing process (RTA) have been studied. Volume fractions for pyrochlore and perovskite were obtained from their respective X-ray diffraction intensities. Two models assuming the starting phase being pure amorphous or pyrochlore were analysed in detail. Equations have been derived and numerical calculation used to simulate the volume fractions for each phase as functions of annealing time. Transformation parameters k and n were obtained by comparing experiment with simulation using a least-squares curve fitting technique.
Keywords: PST; pyroelectric; phase transformations; kinetics